Interdigitating dendritic cell sarcoma of salivary gland associated lymphoid tissue not associated with HHV-8 or EBV infection. Issue 1 (23rd December 2003) - Barwell, N; Howatson, R; Jackson, R; Johnson, A; Jarrett, R F; Cook, G
Abstract : Interdigitating dendritic cell sarcoma (IDCS) is an extremely rare malignancy derived from professional antigen presenting cells. This report describes a case of IDCS arising in the salivary gland associated lymphoid tissue of the parotid gland of a 51 year woman, presenting with a painless neck swelling. Histologically, sheets of S100 + /Ccd68 + /CD45 + /CD34 − /CD1a − spindle cells were surrounded with an inflammatory infiltrate with no evidence of B or T cell clonal proliferations. No evidence of either human herpesvirus 8 or Epstein-Barr virus could be detected by quantitative polymerase chain reaction in the tumour cells with serological evidence of previous Epstein-Barr virus infection. The patient remains well and disease free 24 months after presentation without specific treatment.